2020
DOI: 10.1136/bmjopen-2019-034412
|View full text |Cite
|
Sign up to set email alerts
|

Asylum seekers’ and Refugees’ Changing Health (ARCH) study protocol: an observational study in Lebanon and Denmark to assess health implications of long-distance migration on communicable and non-communicable diseases and mental health

Abstract: IntroductionBy end of 2018, the European Union countries hosted approximately 2.5 million refugees and Lebanon alone hosted more than 1 million. The majority of refugees worldwide came from Syria. The prevailing study design in published studies on asylum seekers’ and refugees’ health leaves a number of fundamental research questions unanswerable. In the Asylum seekers’ and Refugees’ Changing Health (ARCH) study, we examine the health of a homogeneous group of refugees and asylum seekers in two very different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

5
0

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 93 publications
0
12
0
Order By: Relevance
“…The present study found a lower prevalence of preeclampsia among refugee women than native women. One possible explanation for this is the “healthy migrant effect”, where people of refugee/migrant status have more favorable health outcomes compared with the native population in the host countries 33,34 . Reasons for this may be an average younger age in the refugee population at time of giving birth, which is known to lower the risk of developing preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The present study found a lower prevalence of preeclampsia among refugee women than native women. One possible explanation for this is the “healthy migrant effect”, where people of refugee/migrant status have more favorable health outcomes compared with the native population in the host countries 33,34 . Reasons for this may be an average younger age in the refugee population at time of giving birth, which is known to lower the risk of developing preeclampsia.…”
Section: Discussionmentioning
confidence: 99%
“…In some of the studies, no clear definition of refugees is provided, and thus no clear distinction between refugees and migrants. This is problematic as “migrants” is a very heterogeneous term 9,34 . Many factors, such as the reason for migration and the migration process itself, are important to consider, and these can differ substantially between refugees and other types of migrants.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study was part of the “Asylum seekers’ and Refugees’ Changing Health” (ARCH) project which is described in detail in the study protocol ( Eiset et al., 2020 ). Briefly, adult Syrian asylum seekers were included shortly after arriving in Denmark during 2016 through 2018 using a cross-sectional design with one-stage cluster sampling, setting the design effect to one due to random allocation to the asylum centres [22].…”
Section: Methodsmentioning
confidence: 99%